Paralytic Ileus in Post Appendicectomy Patients - WASEEM MUHAMMAD, FAZAL AHMED (Journal of Fatima Jinnah Medical University, 2018)
Background: Surgery is associated with innate risks. Post-operative Ileus is one of the most frequent complication post-operatively following bowel surgery. The peristaltic movements of the intestine recover within 12hours completely. The effect of Epidural anesthesia and General anesthesia both on postoperative ileus has been proved many years ago . Hence the two mode of anesthesia were compared in our research. Study design is Comparative. Patients having acute appendicitis were selected as it is the commonest emergency procedure. Moreover increase sample size helped to reduce sample bias. Objective: The main aim of the study was to compare the effects of Epidural and General Anesthesia reducing time of Paralytic Ileus postoperatively. Methodology: A total of 500 patients were studied having acute appendicitis . All the patients having acute appendicitis were admitted in the Surgical A unit of District Head Quarter Hospital ,Kohat from April 2012 to April 2014. The patients were divided in two groups. Patients having Age >30yrs and those having comorbidies like Appendicular Mass were excluded from the study. Post-operative Ileus and vomiting was observed at 3,6,9 and 12 hrs respevtively and results analyzed using spss 17. Results: 500 patients were divided in two groups Group A and Group B. Mean Age was found to be 25 years in both the groups. Group A was operated using Epidural anesthesia while group B patients underwent General anesthesia. Both groups were observed for recovery of the bowel sounds at 3, 6, 9 and 12 hrs. In Group A patients bowel sounds of 150 patients (60%) recovered at 6 hrs, 60 patients (24%) at 3 hrs, 30 patients (12%) at 9 hrs and in 10 (4%)patients till 12 hours. In Group B 10(4%) patients recovery of bowel motility was within 3 hrs, 175 (70%) patients bowel sounds were audible after 9 hrs, 40 patients(16%) at 6hrs and30 patients (12%)bowel at 12 hrs. Also 50(20%) in Group A developed postoperative vomiting and in Group B vomiting was reported in 115(46%) patients. Conclusion: Results of this study showed that use of epidural anesthesia reduces post- operative ileus in appendectomy patients